URGENSI USHUL FIQH DAN PERSOALAN KONTEPORER - Eko Sariyekti (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2022)
Talking about contemporary issues never seems to run out and always exist. Contemporary problems that we often call contemporary fiqh is the science of sharia laws that are amaliah (practical) from dalil tafshili (detailed) to the latest problems or problems, starting from the beginning of the modern era to modern times which include the current era. In studying contemporary problems, certain skills are needed in choosing and applying Ushul Fiqh, which has a great influence on contemporary problems. This paper discusses the urgency of Ushul Fiqh and its application to real problems that occur in the current contemporary era, where Muslims are faced with increasingly complex and diverse problems.